Vulnerability, impact and adaptation strategies of female farmers to climate variability - Siphosethu Dibakoane; Pakama Siyongwana; Ayanda N. Shabalala (Jàmbá, 2022)
In Africa, agriculture, particularly crop production, is a vital livelihood practice for women, who provide a larger proportion of the labour force. However, the high reliance on rain-fed agriculture, coupled with other socio-economic constraints, exposes female farmers to climatic risks. This paper investigates the participation of women in crop production, key challenges and their coping strategies for climatic disturbances. Drawing on the experiences of female farmers of Thaba Chweu Local Municipality (TCLM) in Mpumalanga, South Africa, the study blended qualitative and quantitative approaches to gather data on their vulnerability and adaptation strategies to climatic shocks. A questionnaire administered through face-to-face interaction and online surveys was the main instrument used to obtain data. This study revealed diverse challenges faced by female farmers in the form of high susceptibility to climatic disruptions, limited funding and gaps in accessing agricultural inputs and equipment (machinery, seeds and fertilisers) and pests. The effects of climate variability manifest in low crop outputs and inferior yields, food insecurity and loss of revenue. The most preferred coping strategies are changing planting and harvesting dates, followed by eating less food, looking for jobs and crop rotation. Although the main source of support comes from both family and government, the majority of the female farmers do not use modern scientific-based and input-intensive agricultural coping strategies such as the use of irrigation systems because of lack of livelihood assets and lower literacy levels.